2016
DOI: 10.1002/chem.201605336
|View full text |Cite
|
Sign up to set email alerts
|

Vicinal Difluoroalkylation and Aminosulfonylation of Alkynes under Photoinduced Conditions

Abstract: A photoinduced vicinal difluoroalkylation and aminosulfonylation of alkynes under photocatalysis was realized. The combination of ethyl 2-bromo-2,2-difluoroacetate, alkynes, and DABCO⋅(SO ) with hydrazines, catalyzed by 9-mes-10-methyl acridinium perchlorate in the presence of visible light, afforded (E)-ethyl 2,2-difluoro-4-aryl-4-sulfamoylbut-3-enoates in good yields with high stereoselectivity. This four-component reaction proceeds through radical addition with the insertion of sulfur dioxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 112 publications
(24 reference statements)
0
28
0
1
Order By: Relevance
“…[90b] On the other hand, Rastogia nd colleagues have proposed an intramolecular photocatalyzed difluoromethylation-cyclization of 1,3-diarylpropynones towards the synthesis of difluoromethylated indenones. [90c] Wu and collaborators [91] introduced in 2017 ap hotocatalytic difluoromethylation four-component multistep reaction with excellent atom economy.The reaction involves avicinal difluoroalkylation and aminosulfonylationo fa lkynes. The tandem radicalprocess is depicted in Scheme 34.…”
Section: Difluoromethylation Of Càct Riple Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…[90b] On the other hand, Rastogia nd colleagues have proposed an intramolecular photocatalyzed difluoromethylation-cyclization of 1,3-diarylpropynones towards the synthesis of difluoromethylated indenones. [90c] Wu and collaborators [91] introduced in 2017 ap hotocatalytic difluoromethylation four-component multistep reaction with excellent atom economy.The reaction involves avicinal difluoroalkylation and aminosulfonylationo fa lkynes. The tandem radicalprocess is depicted in Scheme 34.…”
Section: Difluoromethylation Of Càct Riple Bondsmentioning
confidence: 99%
“…The authors [91] studied the mechanism of this multicomponent reactiono fa lkynes, and DABCO(SO 2 ) 2 with hydrazines, adding TEMPO. As expected,t he reactioni st erminated in the presenceo f2 .0 equiv of TEMPO.…”
Section: Difluoromethylation Of Càct Riple Bondsmentioning
confidence: 99%
“…Further exploration revealed that alkyl–X bond could be dissociated under visible light irradiation in the presence of photoredox catalyst. The photoinduced vicinal difluoroalkylation and aminosulfonylation of alkynes under photocatalysis could be accomplished through a multicomponent reaction of ethyl 2‐bromo‐2,2‐difluoroacetate, alkynes, DABCO · (SO 2 ) 2 , and hydrazines catalyzed by 9‐mes‐10‐methyl acridinium perchlorate in the presence of visible light (Scheme ) . This four‐component reaction was highly effective, affording ( E )‐ethyl 2,2‐difluoro‐4‐aryl‐4‐sulfamoylbut‐3‐enoates in good yields with excellent chemoselectivity and stereoselectivity.…”
Section: Photo‐initiated Formation Of Radical With the Subsequent mentioning
confidence: 99%
“…[13] With the development of organic synthesis, rapid progress has been witnessed with the fixation of sulfur dioxide by using inorganic sulfites or the sulfur dioxide surrogate of 1,4diazabicyclo[2.2.2]octane-sulfur dioxide [DABSO: DABCO-bis(sulfur dioxide)] as the source. [14,15] These methods provide efficient protocols for various synthetically difficult pharmaceutical targets. [16] As useful sulfonylation reagents, sodium sulfinates are widely applied to build various functional sulfonyl-containing compounds, such as sulfonamides and sulfones.…”
Section: Introductionmentioning
confidence: 99%